Strategic Communication Challenges for Museums in the Digital Age - Gonzalez Liendo, Julio Alexander; Gómez Nieto, Begoña (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Understanding the strategic nature of communication is essential for achieving institutional objectives, not only because of the preponderance it must have but also the profile of those who lead it. Through in-depth interviews with communication experts, the analysis of the functions these units perform and the tools they use, an approach is made to the strategic level given to this area in museums. Based on the ranking of the most visited museums in Spain by El Diario, the number of members of the communication team, professional profiles, experience, and platforms used to exercise communication are analyzed, allowing us to understand how this practice is carried out. It was detected that communication is not centralized in a department, thus reducing its strategic meaning. Furthermore, within the organization chart, the communication units do not have a directive or decision-making nature, preventing aligned and cohesive communication.